Unilateral Absence of Musculocutaneous Nerve with Bilateral Variation in the Formation of the Median Nerve - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Anatomical variations of the brachial plexus and its nerves are common. In this case, during a routine cadaver dissection, we encountered different variations of the brachial plexus. On the right side, there was an absence of musculocutaneous nerve (MCN) and the two roots of the median nerve (MN) united in the upper arm despite the axilla. Flexor muscles of the right arm, i.e., coracobrachialis, biceps brachii and brachialis, were innervated directly by the two different branches from the lateral cord. On the left side, the MCN was present and distributed as usual, but the MN received additional contributions from the lateral cord. Variations in the peripheral nerves are usually prone to iatrogenic injuries and brachial plexus block failure. Precise knowledge of such variations helps clinicians in the correct interpretation of unusual clinical findings, nerve conduction tests and imaging. This case report also shows the importance of vigilant anatomical dissection.